Mutation and selection during the secondary response to 2-phenyloxazolone. - Rada, C (1991)
The most characteristic feature of the mouse antibody response to the hapten 2-phenyloxazolone is the recurrent expression of the light-chain variable region Igk-VO chi 1 gene in its germ-line or mutated configuration. The analysis of somatic mutants of the Igk-VO chi 1 gene reported here indicates that, as found during the primary response, hypermutation is also activated during the secondary response. Somatic mutations in the Igk-VO chi 1 gene increased in sequences obtained at day 14 and day 21 in the primary response and again in the secondary response at days 3, 5, and 7. The ratio of replacement to silent mutations also increased, particularly between days 5 and 7, suggesting that a stage of negative selection operates on new somatic mutants generated in the secondary response. Most Igk-VO chi 1 mutants isolated in the secondary response had the features of selected memory clones (i.e., they carried mutations known to increase binding affinity for the hapten). However, some clones had chain-termination codons, and others had mutations predicting a nonfunctional light chain. At least three and possibly five of these clones also expressed the mutation characteristic of the memory response to 2-phenyloxazolone (His-34----Asn-34/Gln-34). We conclude that after a second antigenic challenge, new somatic variants, including some leading to the loss of antigen binding, are generated by hypermutation of cells derived from the memory pool.